2011
DOI: 10.1124/jpet.111.183053
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Positive Allosteric Modulation of TRPV1 Activation by Vanilloids and Acidic pH

Abstract: Transient receptor potential cation channel subfamily V member 1 (TRPV1) is a high-conductance, nonselective cation channel strongly expressed in nociceptive primary afferent neurons of the peripheral nervous system and functions as a multimodal nociceptor gated by temperatures greater than 43°C, protons, and smallmolecule vanilloid ligands such as capsaicin. The ability to respond to heat, low pH, vanilloids, and endovanilloids and altered sensitivity and expression in experimental inflammatory and neuropathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…We previously demonstrated that MRS1477 exhibits no agonist activity at TRPV1, but potentiates the calcium influx induced by orthosteric vanilloid agonists and TRPV1 stimulation by protons or sensitization by phorbol ester [46,47]. In the previous study, we also observed MRS1477 potentiation of intraperitoneal capsaicin-induced hypothermia [46].…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…We previously demonstrated that MRS1477 exhibits no agonist activity at TRPV1, but potentiates the calcium influx induced by orthosteric vanilloid agonists and TRPV1 stimulation by protons or sensitization by phorbol ester [46,47]. In the previous study, we also observed MRS1477 potentiation of intraperitoneal capsaicin-induced hypothermia [46].…”
Section: Discussionmentioning
confidence: 57%
“…In the previous study, we also observed MRS1477 potentiation of intraperitoneal capsaicin-induced hypothermia [46]. In the present study, we were able to induce analgesia through functional inactivation of peripheral primary afferent nerve terminals similar to the long-lasting effect of the potent TRPV1 agonist RTX, which served as our positive control [8].…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations